Identification and Evaluation of Abused Children at Imam Hossein Hospital - Arabghol, Fariba (Int J High Risk Behav Addict, 2016)
BACKGROUND: Child abuse is a phenomenon that confronts the child, family, and society with irretrievable physical and mental injuries, and its negative effects continue until adulthood. OBJECTIVES: The present study was conducted to identify and evaluate cases of abused children at a medical center. PATIENTS AND METHODS: This is a descriptive-analytic study. The subjects were all children and adolescents who were referred to Imam Hussein hospital within 6 months due to physical or psychiatric reasons and were diagnosed with child abuse and neglect by a child and adolescent psychiatrist. The number of these children was 73. Children and their parents were assessed by schedule for affective disorders and schizophrenia (SADS), Kiddie-SADS, and child abuse and demographic questionnaires. The statistical methods of mean and standard deviation were used to analyze the data. RESULTS: 56 cases (76%) were physically abused, 53 cases (72.6%) were emotionally abused, and 3 cases (12.3%) were neglected. The most common psychiatric disorder in abused children was ADHD (65.8%). The next most common were oppositional defiant disorder, obsessive compulsive disorder, general anxiety disorder, and enuresis. About 80% of the abused children had at least one psychiatric disorder. The most common psychiatric disorders in mothers were general anxiety disorder (34.8%) and depression (33.3%), and in fathers, it was substance abuse (19.7%). CONCLUSIONS: Child abuse is a common phenomenon that relates to psychiatric disorders in the abused child or abuser parents. It seems that on-time identification and appropriate interventions can prevent further negative consequences for the child, family, and society.